2010
DOI: 10.1111/j.1365-2818.2010.03459.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated serial sectioning applied to 3D paper structure analysis

Abstract: SummaryA better understanding of paper properties requires a detailed knowledge about the spatial arrangement of its constituent materials in its structure. This paper presents a novel approach for the analysis of the three-dimensional paper structure at the fibre level. A technique combining a rotary microtome and an optical microscopy was developed allowing serial sectioning of hundreds of cuts. The microscope is fixed on a moveable stage and mounted in front of a microtome. Repeatedly, thin slices are cut o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…More concretely, the morphology of wild-type and genetically altered tomato plants were visualised in order to study abnormal leaf axil patterning [105]. In pilot studies, the capacity of HREM for testing paper quality [28,106] and the fibre arrangement and the formation of keratinocytes seeded on skin replacement material [107] were evaluated. These experiments demonstrated that HREM is not restricted to biomedical research, but has yet-unknown capacities to aid research in many other fields of modern science.…”
Section: Hrem For Other Organic Materialsmentioning
confidence: 99%
“…More concretely, the morphology of wild-type and genetically altered tomato plants were visualised in order to study abnormal leaf axil patterning [105]. In pilot studies, the capacity of HREM for testing paper quality [28,106] and the fibre arrangement and the formation of keratinocytes seeded on skin replacement material [107] were evaluated. These experiments demonstrated that HREM is not restricted to biomedical research, but has yet-unknown capacities to aid research in many other fields of modern science.…”
Section: Hrem For Other Organic Materialsmentioning
confidence: 99%
“…A 2D stitching of micrographs was used to convert the single images to a composite image of the whole region of interest with an overlap of 10%. 13 The region around the needled holes, produced at high needling intensities using zero barb and two barbs, respectively, were studied more closely. One hole in each type of sample is shown, while representative features of two holes in each type of sample are discussed in the results.…”
Section: D Analysis Of the Local Fibre Structurementioning
confidence: 99%
“…Unlike optical profilometry, X‐ray micro‐computed tomography (Micro‐CT) is a versatile technique for studying polymer and paper 3D properties such as fiber orientation, porosity, ink deposition, and adhesiveness and even the presence of strange bodies in the paper structure . However, it is more expensive than other imaging techniques.…”
Section: Advanced Characterization Of Paper Devicesmentioning
confidence: 99%